2021
DOI: 10.1111/ijcp.14351
|View full text |Cite
|
Sign up to set email alerts
|

The application of plan, do, check, act (PDCA) quality management in reducing nosocomial infections in endoscopy rooms: It does work

Abstract: Endoscopy is one of the most important methods for clinical diagnosis and treatment of digestive system diseases. It has the advantages of less pain, simple operation and shortened hospital stay after operation. 1 However, the complex structure of the endoscope contains many delicate and small components, making that the endoscope is not easy to clean. Besides, the frequent crossuse of digestive endoscopes between patients put more challenges and requirements to the disinfection of endoscope. 2 If the disinfec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 32 publications
0
23
0
1
Order By: Relevance
“…Studies have proved that the performance of PDCA theory in nursing work can really put nursing work into practice, improve the connotation of nursing quality service, and improve nursing quality continuously and steadily, so as to improve hospital medical quality [5]. Outpatient surgery is basically a small operation, but at present, due to the large flow of patients and the shortage of nurses in the nursing management of the day operating room, the work is confused and the prevention consciousness is weak, which leads to the poor quality of nursing work in the day operating room [6]. In view of this, in this study, to explore the performance of PDCA process management in the day operation ward and the impact of nursing quality and safety, the research results are reported as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have proved that the performance of PDCA theory in nursing work can really put nursing work into practice, improve the connotation of nursing quality service, and improve nursing quality continuously and steadily, so as to improve hospital medical quality [5]. Outpatient surgery is basically a small operation, but at present, due to the large flow of patients and the shortage of nurses in the nursing management of the day operating room, the work is confused and the prevention consciousness is weak, which leads to the poor quality of nursing work in the day operating room [6]. In view of this, in this study, to explore the performance of PDCA process management in the day operation ward and the impact of nursing quality and safety, the research results are reported as follows.…”
Section: Introductionmentioning
confidence: 99%
“…It is time-sensitive and sequential [ 9 ]. Kong's team [ 10 ] conducted a study on 1020 patients receiving treatment in the endoscopy room, which included 512 patients in the PDCA group, and implemented a series of PDCA cycle management measures. The results found that, compared with the conventional management group, patients who applied the PDCA method had a lower incidence of nosocomial infections, sharp injury, and biological contamination and a higher rate of endoscopic cavity disinfection.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PDCA cycle management is a step-by-step process of dynamic cycle according to the specific situation of each department, making targeted goals and plans, implementing PDCA small cycle and large cycle, gradually improving the quality of nursing work under repeated plan-do-check-action, and, finally, achieving the ideal goal ( 20 ). PDCA cycle is a comprehensive cycle, the four stages are inseparable, and the cycle is continuous, with standardization and institutionalization ( 21 ). In the PDCA cycle, the small cycle is the decomposition and guarantee of the implementation of the large cycle.…”
Section: Discussionmentioning
confidence: 99%